Polypropylene/phosphazene nanotube nanocomposites: Thermal, mechanical, and flame retardation studies. Issue 46 (19th June 2020) - Rangaraj, Vengatesan M.; Singh, Swati; Devaraju, Subramani; Wadi, Vijay S.; Alhassan, Saeed; Anjum, Dalaver H.; Mittal, Vikas
Abstract: In this study, flame retardant polypropylene (PP) nanocomposites with superior mechanical performance have been developed using amine‐functionalized phosphazene nanotubes (APZS, 1–10 wt%) through melt‐blending method. Polypropylene‐ graft ‐maleic anhydride was used as the compatibilizer to attain effective interaction between the nanofiller and the PP matrix. The characterization of amine‐functionalized phosphazene nanotubes (APZS) using solid‐state nuclear magnetic resonance (NMR), X‐ray photoelectron spectroscopy, X‐ray diffraction, fourier‐transform infrared (FTIR), and transmission electron microscopy indicated successful amine functionalization, though structural changes were observed as compared to the unfunctionalized nanotubes. Owing to the covalent polymer‐filler interfacial interactions and resulting in uniform filler dispersion, the nanocomposites exhibited significant enhancement in the tensile modulus up to 5 wt% APZS content (98% increment at 5 wt% content as compared to pure polymer). The addition of a small fraction of APZS (1 wt%) improved the impact strength of the nanocomposite by more than 180%. APZS acted as a weak nucleating agent for PP, thereby leading to enhanced degree of crystallinity (up to 5 wt% APZS content). The thermal stability of the nanocomposites was also enhanced with APZS content. The nanocomposites with 5 and 10 wt% APZS loading exhibited a V0 rating in UL‐94 test, indicating that APZS introduced a robust flame retardancy behavior in the PP nanocomposites. The limiting oxygen index values also confirmed the findings from the UL‐94 analysis. The developed nanocomposites exhibit high potential of use in a wide range of high temperature applications. Abstract : Amine‐functionalized phosphazene nanotubes reinforced polypropylene nanocomposites exhibit excellent mechanical and flame retardation properties.